The Role of ChatGPT in Students academic paper Writing Process - Ihsan Maulana; Durratul Hikmah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores how ChatGPT is used by students in the process of writing academic papers, especially in the context of higher education. In the digital era, many students use AI tools like ChatGPT to help generate ideas, improve grammar, structure paragraphs, and revise their academic writing. This research uses a qualitative descriptive approach by conducting interviews with students of the English Education Department at Nurul Jadid University who actively use ChatGPT during the process of writing their final paper. The findings show that ChatGPT plays a helpful role in several stages of the writing process, such as brainstorming, outlining, developing arguments, and refining language. Students feel that ChatGPT helps make their writing clearer, more structured, and easier to understand. However, the study also found several challenges, including inaccurate references, general or irrelevant answers, the risk of plagiarism, over-dependence, and technical problems like poor internet connections. This research concludes that while ChatGPT can support students in academic writing, it should be used wisely and critically. Students need to be aware of ethical issues and maintain their originality and critical thinking. ChatGPT should act as a writing assistant, not as a replacement for the students’ own effort and understanding.